Desain Ruang Unit Kerja Rekam Medis Berdasarkan Aspek Ergonomi Di Puskesmas Senduro - M Mahbub Jauhar Qolbi; Mochammad Choirur Roziqin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2022)
The comfort of the work environment can help in increasing the work productivity of the officers in providing services at the Public Health Center. The medical record unit workspace at Senduro Public Health Center has not met the comfort aspect due to the narrow condition of the room only measuring 9 m2 so that it has an impact on service and the filing room measuring 7.5 m2 is not in accordance with the minimum standard of 20 m2. Tables, chairs and filing shelves have sizes that are not in accordance with the officer’s anthropometry as well as other facilities and infrastructure that are still not in accordance with the officers’ needs. This type of research uses qualitative methods with data collection techniques through observation, interviews, documentation and brainstorming. The results of the study indicate that it is necessary to design a new medical record work unit space that is adjusted to the standard guidelines and flow of medical record file processing as well as the design of tables. The design of the new medical record work unit measuring 10m x 6m which has been adapted to standards / theories and designed using the SketchUp 3D 2020 application in accordance with ergonomic aspects which include efficiency, health, safety, security and comfort.